2006
DOI: 10.1016/s1028-4559(09)60209-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of the Change in Uterine Fibroids Induced by Treatment with a Gnrh Analog

Abstract: We found that the volumes of the uterus and fibroids decreased significantly after treatment with two consecutive doses (given a month apart) of GnRHa. The 3D color Doppler including a histogram and blood flow parameters is another useful tool for fibroid evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 6 publications
4
17
1
Order By: Relevance
“…Therefore, uterine weights in EGs decreased compared to CG. These findings are consistent with the reports of Chia et al (2006), Sun et al (2007), Jiang et al (2010) and Wei et al (2010). The results need to be further verified through experiments and clinical applications.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, uterine weights in EGs decreased compared to CG. These findings are consistent with the reports of Chia et al (2006), Sun et al (2007), Jiang et al (2010) and Wei et al (2010). The results need to be further verified through experiments and clinical applications.…”
Section: Discussionsupporting
confidence: 93%
“…GnRHa may significantly impact uterine growth and development (Chia et al 2006). It has been reported that the uterine volume reduced following subcutaneous injection of 3.75 mg of GnRHa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations